Digital Transformation of Customer Experience in SMEs Evidence from Hungarian Firms - Pecze, Krisztina; Veszelovits, Bella; Balázsné Lendvai, Marietta; Mosolygó-Kiss, Ágnes (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Small and medium-sized enterprises (SMEs) are key to economic resilience, yet their digital maturity and customer experience (CX) practices differ significantly. Research emphasizes that customer-centric development, data-driven decision-making, and the adoption of emerging technologies -especially artificial intelligence (AI)- are critical for competitiveness and long-term sustainability. This study examines how Hungarian SMEs integrate digital solutions into customer experience management and how these practices enhance performance and innovation. We propose a framework for the digital enablement of CX activities and report findings from a survey with quantitative insights on customer-centric initiatives, digital tool usage, and perceived organizational impact. Particular attention is given to AI-supported solutions, including automated communication, CRM systems, and analytics tools, and their role in process modernization and customer satisfaction. By identifying adoption patterns and perceived effectiveness, the research contributes to a deeper understanding of digital transformation in the SME sector and supports more sustainable, technologically empowered operations.